Pengembangan Aplikasi Inshoot Untuk Anak Berkebutuhan Khusus Dalam Belajar Online di Daerah Padang Panjang Pada Sekolah Dasar - Mathia Ridwan.N; Adam Mudinillah (Program Studi PGMI STAI Daruttaqwa Gresik, 2022)
This paper discusses what applications can be used by children with special needs in online learning. Some of the things in this paper are solutions for children with special needs in online learning because of online learning in almost all parts of the world due to the Covid-19 pandemic. Children with special needs in this case also really need learning media that are able to support these children in online learning. In this case, reading about children with special needs (Autism), as well as the law on the equal rights of children with special needs with normal children. And the role of parents towards children with special needs. This article also explained the difference between children who tend to have the right brain and the left brain. This article also explains the different student learning arrangements for each child. A child who learns in a kinesthetic way will not be able to equate his way of learning with a visual child. Every child has their own strengths, a child who excels in mathematics will not be able to equate his abilities with a child who excels in the arts. This is because everyone has different genetics and has a different way of working the brain.